El proceso contable y su incidencia en la información financiera de la empresa Comagrico S.A. - Pulecio Martínez, Derian Alexander (2020)
The objective of this study is to determine how the Agricola Marketer COMAGRICO S.A carries its accounting process, this entails from the delivery and receipt of the basic documents for the start of the accounting to the financial statements, which must not present inaccuracies or errors of any kind, if it has any software that agilities its agricultural and administrative activities, both agricultural and administrative activities , and that affects the company whether or not it has useful and necessary tools when displaying financial information to its partners and the relevant government entities. The Marketing Company COMAGRICO S.A, although it is a relatively new entity has the predisposition to carry out its work as stipulated by law in terms of regulations and rules to follow to provide the best attention to its customers and to be recognized in the locality, improving day by day with machinery and instruments of excellent quality. For this company it is very important to recruit the right staff because, if you have the human talent required by each position, there would be no mishap when registering the accounting and financial information. Government entities such as SRI, IESS and the Superintendency of Companies always have rules, laws, strategic plans and benefits for companies that recently start activities to prevent them from making mistakes that would harm the owners of the entity and the country in general, such as submitting adulterated financial information to evade taxes. The aim of these government institutions is to reduce fraud and corruption in the least, because if the regulatory is stopped, Ecuador loses, that is, we lose all, because there would be fewer roads, hospitals, schools and our country would remain in development for much longer.